Learning Remo Gagrak Anyar Dance by Sariono At Sanggar Putra Bima Respati - Rahelia, Deby Yovita; Handayaningrum, Warih (Solah, 2025)
Remo Gagrak Anyar dance is an innovative form of East Javanese traditional dance created by Sariono, characterized by more modern movements, accompaniment, and presentation but still maintaining traditional values. At Sanggar Putra Bima Respati Surabaya, learning Remo Gagrak Anyar emphasizes a deep, repetitive, and disciplined process in mastering movement techniques. The approach used is emotional and contextual, through giving praise, encouragement, and personal attention to students. The learning process is carried out in stages starting from warm-up, demonstration, movement practice, to oral and practical evaluation. This study aims to examine the learning of Remo Gagrak Anyar dance by Sariono at the Putra Bima Respati studio. This research uses a qualitative approach with the methods of observation, interviews, documentation, and literature study. The results showed that the learning of Remo Gagrak Anyar Dance in the studio succeeded in creating an adaptive, creative learning atmosphere, and was able to attract the interest of the younger generation. This learning is not only a means of developing skills, but also as an effort to preserve culture through an approach that is relevant to the times.